The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/membranes12030302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nanofiltration Membranes for Pure Lactic Acid Permeability

Abstract: Lactic acid (LA) is an organic acid produced by fermentation or chemical synthesis. It plays a crucial role in the pharmaceutical, food and plastic industries. In the fermentation of, for example, grass silage, LA and different compounds are produced. To purify lactic acid, researchers have tried to investigate membrane technology to achieve a high yield of lactic acid permeance. This study tested four commercially available nanofiltration membranes (NF270, MPF-36, Toray NF, and Alfa Laval NF). Nanofiltration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It is composed of the active layer made from semiaromatic piperazine-based PA and the support layers from polysulfone (PS) and nonwoven polyester (PET) (Figure 4). Table 2 summarizes the physicochemical characteristics of the membrane, as given by the manufacturer, and several studies reported in the literature [31,33,[78][79][80][81][82][83][84][85][86]. During the investigation performed in the present study, the membrane surface was negatively charged since the pH of the fermentation broths (equal to 7) was higher than the isoelectric point of the membrane (equal to 4).…”
Section: Nf Set-upmentioning
confidence: 92%
See 1 more Smart Citation
“…It is composed of the active layer made from semiaromatic piperazine-based PA and the support layers from polysulfone (PS) and nonwoven polyester (PET) (Figure 4). Table 2 summarizes the physicochemical characteristics of the membrane, as given by the manufacturer, and several studies reported in the literature [31,33,[78][79][80][81][82][83][84][85][86]. During the investigation performed in the present study, the membrane surface was negatively charged since the pH of the fermentation broths (equal to 7) was higher than the isoelectric point of the membrane (equal to 4).…”
Section: Nf Set-upmentioning
confidence: 92%
“…(i) The highest rejection of succinic acid is related to the fact that it is a diprotic acid, hence, its separation was based on much stronger electrostatic interactions than in Lactic acid may be produced in two ways: biotechnological process and chemical synthesis [16,79]. However, according to [100], 90% of all lactic acid produced worldwide is derived via fermentation processes and the cost of its separation from fermentation broths can reach 50% of the total process costs.…”
Section: Carboxylic Acids and Ethanolmentioning
confidence: 99%
“…Polylactic acid (PLA) is a type of degradable polymer material with lactic acid as raw material [ 166 , 167 ], which is renewable and has the characteristics of non-toxicity, non-irritation, good biocompatibility, processability, excellent mechanical properties, complete biodegradability and environmental friendliness [ 168 , 169 ], and is considered as the main alternative to petroleum-based plastics [ 170 ].…”
Section: Biodegradable Film Materialsmentioning
confidence: 99%
“…Even in 2010, the U.S. Department of Energy issued a report that listed LA as a potential building block for the future [ 3 ]. There are two main production methods for LA, chemical synthesis, and biological fermentation [ 1 , 4 , 5 ]. Compared with chemical synthesis, biological fermentation can use low-cost biomass waste, such as kitchen waste [ 6 ], straw [ 7 ], and sludge [ 8 ] as substrates for microbial LA fermentation, which is more environmentally friendly, has low energy consumption, and can produce LA with higher optical purity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%